Assessment of prognostic factors affecting functional outcome in spinal tuberculosis patients - S, Harkeerat; Karupiah, Rajandra Kumar; N, Vijayasingham; Zakaria@Mohamad, Zamzuri (2019)
This study was aimed to determine the favorable prognostic factors in spinal tuberculosis patients with significant neurology for their functional outcome.